Diel distribution and feeding habits of Neomysis mirabilis under seasonal sea ice in a subarctic lagoon of northern Japan - K Takahashi (Inter-Research, 2015)
We investigated the diel distribution and feeding habits of the mysid Neomysis mirabilis under seasonal sea ice in a subarctic lagoon of northern Japan. Although large individuals (>11 mm total length) were present in the eelgrass beds regardless of the time of day, smaller individuals only migrated to the eelgrass beds at night, possibly from shallower waters. Investigation of their stomach contents revealed that N. mirabilis is primarily dependent on eelgrass epiphytes as a food source, in addition to small crustaceans. Calculations based on gut pigment analysis indicated that epiphytes were sufficient for large mysids to fulfill their metabolic requirements, whereas small mysids needed to ingest additional food items, such as small crustaceans, possibly because they were less able to graze the highly adhesive prostrate epiphytes. This study suggests that grazing on epiphytes could be a third option in the feeding habits of mysids (in addition to suspension-feeding and predation), and is beneficial in maintaining their high biomass, even during the winter.